2017
DOI: 10.1080/02656736.2017.1293304
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in ovarian cancer patients undergoing cytoreductive surgery and hyperthermic intra-peritoneal chemotherapy

Abstract: Identification of risk factors for AKI post-CRS-HIPEC helps improve pre-operative patient selection and optimisation, facilitate tailoring of chemotherapy, and foster closer peri-operative monitoring and fluid management in at-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
40
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 15 publications
9
40
1
Order By: Relevance
“…Furthermore, obese patients exhibit a higher risk of AKI because of hyperfiltration, increased glomerular capillary wall tension and podocyte stress [25]. Blood transfusions are associated with postoperative AKI in HIPEC surgery [26]. Our study found that the rate of postoperative blood transfusions was higher in patients with AKI.…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, obese patients exhibit a higher risk of AKI because of hyperfiltration, increased glomerular capillary wall tension and podocyte stress [25]. Blood transfusions are associated with postoperative AKI in HIPEC surgery [26]. Our study found that the rate of postoperative blood transfusions was higher in patients with AKI.…”
Section: Discussionmentioning
confidence: 53%
“…In the past decades, several studies have demonstrated an association between ARI after HIPEC and cisplatin-based regimens. A study reported an incidence of overall renal toxicity of 40.4% and an incidence of grade 3-4 renal impairment of 10.6% in ovarian cancer patients treated with cisplatin-based HIPEC regimens according to the criteria of National Cancer Institute -Common Terminology Criteria for Adverse Events (NCI-CTCAE) v.3.0 [4]. Another study reported that 11.1% (11/99) of patients who received HIPEC had a significantly higher risk of ARI and that 10 of these 11 patients received a regimen containing cisplatin (60 mg/m 2 infused for 60-90 min) [5].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, AKI occurred in 40.4% of ovarian cancer patients undergoing CRS and HIPEC. All those patients received cisplatin [ 11 ]. More recently, Cata et al reported a 21.3% incidence of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a handful of studies evaluated the incidence of AKI in patients undergoing cytoreductive surgery with hyperthermic intraperitoneal therapy (CRS and HIPEC) [ [9] , [10] , [11] ]. However, kidney injury related to cisplatin, a known nephrotoxic agent, was a major contributor to the occurrence of AKI.…”
Section: Introductionmentioning
confidence: 99%